Affective engagement concerning belonging and investment in 6th graders in reading in the efl class (2024)
Reading in English is a fundamental element for the academic and professional development of students as it allows for the acquisition of linguistic skills and opens doors to job opportunities. Therefore, engagement in reading in English is crucial to fostering a sense of belonging and investment in reading. This study described the sense of belonging and investment of sixth-grade students from a public school in Monteria through the analysis of their experiences with reading from primary to secondary school. This study used a narrative inquiry method to collect the students' stories related to reading and employed various data techniques such as students' written narratives that were collected during one writing session to research about students’ personal stories, nine interviews, and five observations, which allowed us to characterize the students' sense of belonging and investment in the English class. The findings of this research showed students’ sense of belonging and investment is very low concerning English reading. In turn, when reading in Spanish it drastically changes positively. For example, students' preferences in reading are not connected with their reading activities in classes. Results delved into a need for planning reading materials and strategies that are aligned with students’ reading narratives or experiences as well as the creation of an environment that provides diverse and interesting reading materials for them.